Contribution to the phycological study of the Balearic Islands. III. Rhodophyceae - Ribera Siguán, M. A.; Gómez Garreta, A.; Seoane Camba, A. (Lazaroa, 2014)
In this note, that is part of the algologic study that we are doing in the Balearie lslands, we cite sixteen new Rhodophyceae in the archipelago, from which we point out: Contarinia peyssonneliaeformis Zanard., Peyssonnelia borneii) Boudouresque et Denizot, Peyssonnelia rosa-marina Boudouresque et Denizot, Griffithsia opuniloides J. Agardh and Seirospora sphaerospora J. Feldmann that are new in the Spanish mediterranean coast.